Falling towards the centre - Maluleke, Vuyelwa (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2020)
I am interested in the poem as a textual body that is able to collect the ruptures, silences, music, and wounds of the body, Ukuzithutha, in order to perform their address. I seek to assemble these disfigured and fractured bodies, of which I am one, onto the page. And thus create an experimental, non-linear lyric of repetitions and fragmentations arranged into a memory text, to hold these stories against what Audre Lorde calls 'the tyranny of silence'. My thesis is influenced by Ntozake Shange's choreopoem, 'for colored girls who have considered suicide when the rainbow was enough', Claudia Rankine's 'Don't let me be Lonely', Sindiswa Bukusu's 'Loud and yellow laughter'. And Fiona Benson's 'Vertigo and Ghost' whose form and lyric is a strong influence on the shape of the manuscript, and the construction of its mythologies.
Keywords: South African fiction (English) -- 21st century